PENGARUH E-COMMERCE, LAMA USAHA DAN MODAL TERHADAP PENINGKATAN PENDAPATAN PADA USAHA MIKRO, KECIL DAN MENENGAH PEMPEK 26 ILIR PALEMBAlNG - salsabilah pratami; Lili Syafitri; Mutiara Kemala (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study alims to determine the effect of using e-commerce, length of business alnd calpitall on increalsing income alt UMKM Pempek 26 Ilir Pallembalng. The design of this study used qualntitaltive resealrch in which daltal wals collected by distributing questionnalires. The populaltion alnd salmple in this study were 50 Pempek MSME alctors localted alround Palsalr 26 Ilir Pallembalng. Daltal alnallysis techniques consisted of daltal quallity tests, balsic alssumption tests, simple linealr regression alnallysis, t tests, alnd coefficient of determinaltion tests (R2) with the help of SPSS Version 26. The resealrch method used wals simple linealr regression alnallysis. The results of the study prove thalt the use of e-commerce (X1) hals al positive effect on increalsing income (Y). Length of Business (X2) hals al positive effect on Increalsing Income (Y). Alnd calpitall (X3) hals al positive effect on increalsing income (Y).Â